Maharah Qiraah Learning Practices Using Al Ashri Book: Amalan Belajar Maharah Qiraah Menggunakan Kitab Al Ashri - Abdul Baqiy; Khizanatul Hikmah (Universitas Muhammadiyah Sidoarjo, 2025)
General Background Arabic language instruction in secondary education emphasizes reading competence as a core linguistic skill required for understanding written texts and religious sources. Specific Background At Muhammadiyah 2 Sidoarjo High School, maharah qira’ah learning relies on the Al-Ashri textbook as the primary instructional resource, supported by varied teaching strategies and classroom media. Knowledge Gap Existing studies have discussed maharah qira’ah learning strategies, yet limited qualitative analysis focuses on instructional preparation, classroom implementation, evaluation procedures, and contextual learning factors using the Al-Ashri book at the senior high school level. Aims This study aims to describe teacher preparation, instructional implementation, evaluation practices, and supporting and inhibiting factors in maharah qira’ah learning using the Al-Ashri book. Results The findings show that teachers prepared structured lesson modules aligned with the textbook, applied drill, discussion, and communicative methods supported by PowerPoint media, games, and additional texts, and conducted formative and summative evaluations. Inhibiting factors included students’ diverse educational backgrounds and limited prior Arabic knowledge, while supporting factors consisted of the Quran Reading Team program and game-based learning activities. Novelty This study provides a comprehensive qualitative portrayal of maharah qira’ah learning processes centered on the Al-Ashri book in a Muhammadiyah senior high school context. Implications The findings offer practical insights for Arabic language educators in managing instructional strategies and addressing learner diversity in reading instruction. Highlights: Instructional planning was systematically aligned with textbook structure and learning objectives. Classroom activities combined repetitive practice, interaction, and visual support to facilitate reading activities. Learner background diversity shaped both instructional challenges and classroom support strategies. Keywords: Maharah Qiraah, Arabic Reading Instruction, Al Ashri Boo, Qualitative Analysis, Senior High School